A Single Species of Clostridium Subcluster XIVa Decreased in Ulcerative Colitis Patients. Issue 12 (December 2016) - Takeshita, Kozue; Mizuno, Shinta; Mikami, Yohei; Sujino, Tomohisa; Saigusa, Keiichiro; Matsuoka, Katsuyoshi; Naganuma, Makoto; Sato, Tadashi; Takada, Toshihiko; Tsuji, Hirokazu; Kushiro, Akira; Nomoto, Koji; et al.
Abstract : Background: Imbalance of the intestinal microbiota is associated with gastrointestinal disease and autoimmune disease and metabolic syndrome. Analysis of the intestinal microbiota has recently progressed, and the association with inflammatory bowel disease has been reported at the species level. Such findings suggest that the recovery of homeostasis in the intestinal microbiota could cure inflammatory bowel disease. We aimed to search new probiotic candidates for inflammatory bowel disease through translational research by analysis of ulcerative colitis (UC) patients' intestinal microbiota and clarify the effects of them on inflammation. Here, we focused on Fusicatenibacter saccharivorans, which belongs to Clostridium subcluster XIVa and was successfully isolated and cultured in 2013. We analyzed the association of F. saccharivorans to UC patients' activity and inflammation for the first time. Methods: Feces from UC patients and healthy controls were analyzed by 16S ribosomal RNA gene sequences. F. saccharivorans was administered to murine colitis model. Colitic lamina propria mononuclear cells from UC patients and mice were stimulated with F. saccharivorans . Results: The whole fecal bacteria in active UC patients were less than that in quiescent UC patients. Furthermore, F. saccharivorans was decreased in active UC patients and increased in quiescent. The administration of F. saccharivorans improved murine colitis. F. saccharivorans induced interleukin 10 production by lamina propria mononuclear cells from not only colitis model mice but also UC patients. Conclusions: F. saccharivorans decreased in correlation to UC activity and suppresses intestinal inflammation. These results suggest that F. saccharivorans could lead to a novel UC treatment. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 8 November 2016.